How to Make Money in Stocks: A Winning System in Good Times and Bad, Third Edition - O'Neil, William (McGraw-Hill, 2002)
Investing, CAN SLIM investing, portfolio, retirement planning, wall street, Dow Jones, NASDAQ, profit, dividend, financial planning, stocks, making money.